Legal Education and Reproductive Education as An Efforts to Prevent Sexual Violence in Celikah Village, South Sumatra - Banjarani, Desia Rakhma; Adnindya, Msy Rulan; Pasyah, Taroman; Nugraha, Muslim (Faculty of Law Pattimura University, 2026)
Introduction: The high rate of sexual violence in rural areas demonstrates that this issue is not solely related to the perpetrator's behavior, but also to the community's lack of understanding of victims' legal rights and reproductive health. Therefore, structured, sustainable, and contextualized legal and reproductive education is needed, in keeping with the social and cultural values of rural communities.Purposes of The Devotion: So that village officials can form or create new policies that are needed to prevent and overcome sexual violence in the Celikah Village area.Method of The Devotion: The activity model in the form of legal counseling uses a visitation model, namely a community service activity carried out by the Counseling Team of Lecturers from the Faculty of Law, Sriwijaya University visiting the target audience of the Celikah Village community, Kayu Agung District, Ogan Komering Ilir Regency. The legal counseling team in this activity uses 2 (two) methods, namely: Presentation and question and answer discussion.Results Main Findings of the Devotion: The